COMMUNICATIVE ACTIVITY AS A PEDAGOGICAL PROBLEM - Древняк, Лада (SWorldJournal, 2023)
This article draws attention to the relevance of the problem of communicative development, reveals the essence of the concept of communicative activity, draws a parallel between the definitions of the concepts of communication and communicative activity,